1966
DOI: 10.1111/j.1600-0609.1966.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

The Periodic Acid‐Schiff Reaction in Neutrophil Leukocytes in Chronic Myeloproliferative Diseases A microspectrophotometric study

Abstract: Microspectrophotometric quantification of the PAS reaction has been carried out in about 4500 individual mature neutrophil leukocytes from 20 normal persons, and from 15 patients with chronic myelocytic leukaemia (CML), 18 patients with myeloid metaplasia, and 17 patients with polycythaemia vera (PV). The reaction is considered to be a quantitative measure of the amount of PAS reactive material (PASMa) in neutrophils, most of it probably glycogen. Neutro‐phils from CML had a mean amount of PASMa that was 39 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

1966
1966
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…Whether the PV granulocyte is activated or not is controversial. Some, but not all, previous studies have suggested that resting PV PMNs may have higher oxidative metabolism, phagocytosis and glycogen metabolism (1)(2)(3)(4)(5). We could not detect any deviation from normal PMNs with regard to spontaneous CL.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Whether the PV granulocyte is activated or not is controversial. Some, but not all, previous studies have suggested that resting PV PMNs may have higher oxidative metabolism, phagocytosis and glycogen metabolism (1)(2)(3)(4)(5). We could not detect any deviation from normal PMNs with regard to spontaneous CL.…”
Section: Discussioncontrasting
confidence: 69%
“…Thus, Wagner (1) found an increased glycogen content in PMNs from patients with PV, and a 1.5 times greater rate of glycogen turnover was reported by Luganova & Seitz (2). A mean increase of 33% in PAS-reactive material in PV granulocytes was noted by Gahrton (3). Enhanced phagocytosis of yeast (4) and of polystyrene particles ( 5 ) has also been shown.…”
mentioning
confidence: 87%
“…The control material consisted of 20 normal subjects previously reported (Gahrton 1966~). Both blood and bone marrow neutrophils were studied repeatedly in one of these cases.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%
“…P A S staining. The McManus PAS reaction (Mc Manus & Mowry 1960) was performed as previously modified (Gahrton 1964(Gahrton , 1966: 0.5 % periodic acid for 60 minutes; distilled water for 3 minutes (1 minute in each of three rinses); Schiff reagent (Fuchsin-Sulphurous Acid Test Solution, Harleco, Hartmann-Leddon Company, Philadelphia, Pa.) for 60 minutes; sulphuric acid rinse (10 % sodium metabisulphite 6 ml., normal hydrochloric acid 5 ml., distilled water 100 ml.) for 6 minutes (2 minutes in each of three rinses); rinsed in running tap water for 5 minutes; rinsed in distilled water for 30 seconds.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation